Outcomes in, and characteristics of, patients who undergo intrauterine insemination immediately after failed oocyte retrieval - Pietro Bortoletto, M.D; Stephanie F. Willson, M.D; Phillip A. Romanski, M.D; Owen K. Davis, M.D; Zev Rosenwaks, M.D (Elsevier, 2020)
Objective: To describe the patient and cycle characteristics of women who undergo intrauterine insemination (IUI) immediately after an unsuccessful oocyte retrieval. Design: Retrospective case series. Setting: University-affiliated center. Patient(s): Women who underwent an oocyte retrieval procedure in which no oocytes were retrieved followed by an IUI on the same morning. Intervention(s): None. Main Outcome Measure(s): Live birth rate, subsequent live birth rate. Result(s): From 2011 to 2019, 63 cycles in 57 patients were identified. The mean (SD) age was 39.6 (4.6) years, and diminished ovarian reserve (94.7%) was the most common diagnosis. The median (IQR) number of previous IVF cycles in this cohort was 3 (1-7), with 56.1% having had at least one previous canceled IVF cycle. The majority of patients had undergone either controlled ovarian hyperstimulation (COH) (64.9%) or modified natural cycles (21.1%). The mean (SD) number of follicles >14 mm at the time of trigger was 1.9 (1.4), with 38.9% of patients manifesting a drop in their estradiol levels after the trigger. One pregnancy resulting in a live birth was identified (1.8%). For patients who underwent subsequent IVF cycles, 60.7% had at least one subsequent cancelled cycle. Three patients went on to achieve a live birth using autologous oocytes (6.5%). Conclusion(s): Same-day IUI for patients who have no oocytes retrieved is associated with a <2% chance of achieving a live birth. Of patients who attempt subsequent IVF cycles, nearly two thirds will go on to have at least one subsequent cancelled cycle. In this poor-prognosis cohort, fewer than 10% will ultimately achieve a live birth by the use of autologous oocytes.